2000
DOI: 10.1001/archinte.160.8.1142
|View full text |Cite
|
Sign up to set email alerts
|

Patient Comprehension and Reaction to Participating in a Double-blind Randomized Clinical Trial (ISIS-4) in Acute Myocardial Infarction

Abstract: Despite proper attention to accepted ethical and legal standards, perceived patient comprehension in this trial in acute myocardial infarction was incomplete or lacking in a considerable number of subjects. Much progress must be made toward the goal of true informed consent in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
1
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 33 publications
(30 reference statements)
3
60
1
5
Order By: Relevance
“…In other studies including patients with acute myocardial infarction, the rates of lack of recall were similar to our rate. However, the informed-consent procedures were performed in a more stressful and urgent condition than was our consent procedure [16,17]. In our study, as many as 25% of patients had incomplete recall of the study components.…”
Section: Discussionmentioning
confidence: 73%
“…In other studies including patients with acute myocardial infarction, the rates of lack of recall were similar to our rate. However, the informed-consent procedures were performed in a more stressful and urgent condition than was our consent procedure [16,17]. In our study, as many as 25% of patients had incomplete recall of the study components.…”
Section: Discussionmentioning
confidence: 73%
“…Verbal information is understood and retained significantly better by patients compared with written information in acute MI trials. [54][55][56] The assent procedure was successfully used in the Strategic Reperfusion Early after Myocardial Infarction (STREAM) 57 and the Reperfusion Facilitated by Local adjunctive therapy in STEMI (ReFLO-STEMI) 58 multicentre acute STEMI studies. If patients met the inclusion criteria after angiography they were asked to give further verbal assent before randomisation.…”
Section: Initial Assessment and Assentmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] A particular concern is that some patients do not have the requisite skill, numeracy, to understand and manipulate quantitative information about uncertain outcomes. For example, in a study of highly educated adults, Lipkus et al 12 found low levels of numeracy, with no more than one-third of respondents able to answer all 10 items correctly on the authors' numeracy scale.…”
mentioning
confidence: 99%